2016
DOI: 10.18632/oncotarget.10780
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 is a potential molecular marker of natural killer/T-cell lymphoma

Abstract: Natural killer/T-cell lymphoma (NKTCL) is characterized by its highly aggressive nature and rapid progression. MicroRNAs (miRNAs) play key roles in the development of NKTCL. We utilized next-generation Solexa high-throughput sequencing to compare miRNA expression in the SNK-6 and YTS NKTCL cell lines with expression in normal NK cells. We found that 195 miRNAs were upregulated in the SNK-6 cells and 286 miRNAs were upregulated in the YTS cells. Based on those results, we selected six miRNAs, including miRNA-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…87 Zhang and colleagues observed significantly higher miR-155 levels in the serum of NKTCL patients compared with the levels in healthy individuals. 70 More importantly, serum miR-155 levels were higher in patients with stable or progressive disease compared with those in partial or complete remission. 70 Two distinct studies reported an inverse relationship between ASNS (asparagine synthetase) expression level and response to asparaginasebased chemotherapy in NKTCL cell lines and patient samples.…”
Section: Ebv-induced Alterations In Nktcl Epigenomesmentioning
confidence: 96%
“…87 Zhang and colleagues observed significantly higher miR-155 levels in the serum of NKTCL patients compared with the levels in healthy individuals. 70 More importantly, serum miR-155 levels were higher in patients with stable or progressive disease compared with those in partial or complete remission. 70 Two distinct studies reported an inverse relationship between ASNS (asparagine synthetase) expression level and response to asparaginasebased chemotherapy in NKTCL cell lines and patient samples.…”
Section: Ebv-induced Alterations In Nktcl Epigenomesmentioning
confidence: 96%
“…62 In addition, mir155 overexpression led to the expansion and activation of NK-cells in vivo. 63 Intriguingly, mir155 has recently been reported to be overexpressed in NKTCL, 64 and its overexpression may account for the activation of AKT pathway observed previously by DNA microarray in NKTCL cases. 58 These observations suggest that loss-of-function of PRDM1 may, at least in part, be responsible for mir155 overexpression in NKTCLs.…”
Section: Discussionmentioning
confidence: 78%
“…SEM analysis indicates the clustering of MNPs (Figure S2, Supporting Information) due to the polar nature of fatty acid functional groups applied on their surfaces. Surface functionalization of MNPs is a key aspect in developing magnetic scaffolds, because without it the MNPs would induce genotoxic behavior in tissues and cause necrosis of the cells with which it comes into contact . Fatty acids like oleic acid have been used to coat the surface of MNPs to render the ferrofluid into a stable, biocompatible, colloidal solution .…”
Section: Resultsmentioning
confidence: 99%